Do workers benefit from competition? evidence from the Philippines in the years 2014 and 2015 - Ferrer, Jose Mari III L. (School of Economics, University of the Philippines Diliman, 2018)
This paper measures the effect of the level of competition on the real wages of employees across Philippine industries in the years 2014 to 2015. The initial hypothesis is that the lack of competition in Philippine industries could be a driving factor in the relative stagnation of real wages in the Philippines, compared to increasing labor productivity. With this, we hypothesize that the level of competition in an industry and the real wages of workers in said industry have a positive relationship. Data was gathered from the Annual Survey of Philippine Business and Industry (ASPBI), the Labor Force Survey (LFS) and the quarterly Consumer Price Index (CPI) reports, all taken from the website (for aggregate data) and data enclave (for firm_specific data) of the Philippine Statistics Authority. Three Heckman two_stage regression models were used to estimate the effects of said competition on labor productivity, with three different measures of industry competition used_ the number of firms in an industry, the log of the inverse of the number of firms in an industry, and the four_firm concentration ratio per industry. The empirical results show that as competition in an industry increases, the real wages of employees increase, affirming the initial hypothesis.